2020
DOI: 10.1007/s42452-020-03562-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and inorganic fertilization on growth, yield, seed fixed oil content, and fatty acids profile of garden cress (Lepidium sativum L.)

Abstract: In the present study, a field experiment was conducted for two consecutive seasons (2016/2017 and 2017/2018). The effects of organic and inorganic fertilization on growth, seed yield, seed fixed oil yield, and fatty acid profile of garden cress (Lepidium sativum L.) were investigated under conditions of Khartoum State, Sudan. In each season, the experiment was laid out in a randomized complete block design with four replications. Four fertilizer treatments were used; these were chicken manure at a rate of 11.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…TP also played an important role in these parameters, as demonstrated by correlations at the level of p < 0.001 and p < 0.01 for virtually all combinations (Figure 13). The influence of these elements on the growth of L. sativum was also reported by Mohamed et al [74]. The results of the current study concerning L. sativum root length, measured after two and four days, indicated that this parameter was most sensitive to potentially harmful compounds occurring or resulting from changes in organic matter introduced with SMS and M in soil solution.…”
Section: Discussionsupporting
confidence: 86%
“…TP also played an important role in these parameters, as demonstrated by correlations at the level of p < 0.001 and p < 0.01 for virtually all combinations (Figure 13). The influence of these elements on the growth of L. sativum was also reported by Mohamed et al [74]. The results of the current study concerning L. sativum root length, measured after two and four days, indicated that this parameter was most sensitive to potentially harmful compounds occurring or resulting from changes in organic matter introduced with SMS and M in soil solution.…”
Section: Discussionsupporting
confidence: 86%
“…The result of this study also stated that increasing level of nitrogen the oil yield in seeds of chandrasur also increase. These results are in agreement with those establishing that fertilization increases the fatty acid presence, percentages and the fattyacids ratio in canola seed oil [7,8].…”
Section: Oil Yield (Kg Ha -1 )supporting
confidence: 93%
“…When we consider the decrease in leaf area, however, it can be said that the amount of chlorophyll in the control plants were higher than the other treatments. Chlorophyll is essential in the process of photosynthesis and is responsible for vegetative growth (Mohamed et al, 2020). Decreased chlorophyll a and b in plant leaves may also affect photosynthetic performance, which may reduce plant growth (Ehsan et al, 2014).…”
Section: Resultsmentioning
confidence: 99%